2016
DOI: 10.1093/humrep/dew307
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of endometrial polyps

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 19 publications
2
21
0
1
Order By: Relevance
“…Immediately after ultrasound diagnosis of an endometrial polyp, according the guidelines for the treatment of endometrial polyps >10 mm, operative hysteroscopic polypectomy was undertaken excluding also any other coexisting pathology in the uterine cavity. 4,14,15 …”
Section: Methodsmentioning
confidence: 99%
“…Immediately after ultrasound diagnosis of an endometrial polyp, according the guidelines for the treatment of endometrial polyps >10 mm, operative hysteroscopic polypectomy was undertaken excluding also any other coexisting pathology in the uterine cavity. 4,14,15 …”
Section: Methodsmentioning
confidence: 99%
“…It is a benign hyperplastic overgrowth of endometrial glands and stroma affecting 7.8% to 50% of women, with a prevalence of malignancy ranging from 1 to 3%, particularly in post-menopausal patients [97][98][99][100][101][102][103]. Spontaneous regression has been reported in 6.3 to 25% of cases [97,104]. Although its etiopathogenesis is still unknown, it is usually presented as a hormone-related condition [103,105,106].…”
Section: The Concept Of Impaired Inflammatory State Of the Endometriummentioning
confidence: 99%
“…They are a recognized cause of abnormal vaginal bleeding and have also been associated with subfertility and early pregnancy loss,. The ultrasound features of benign polyps in non‐pregnant women have been well‐documented, but there have so far been no reports of endometrial polyps identified on ultrasound examination during early pregnancy.…”
Section: Demographic Data Size Of Polyp and Pregnancy Outcome In Wommentioning
confidence: 99%